Las ambigüedades del pensamiento político rousseauniano y el debate sobre su «influencia» en varios protagonistas de las independencias hispanoamericanas - Roberto Breña (Cuadernos de Ilustración y Romanticismo)
This article shows, on its first half, some of the more important ambiguities and inconsistencies of the political thought of Rousseau. In its second half, it reviews the historiography that has dealt with the purported «influence» of this thought over some of the protagonists of the Spanish American independence movements. The conclusion of the article is that this «influence» is much less than what several historians have asserted.